2006
DOI: 10.1590/s0102-33062006000200003
|View full text |Cite
|
Sign up to set email alerts
|

Produção de metabólitos bioativos pelo líquen Cladonia substellata Vainio

Abstract: RESUMO -(Produção de metabólitos bioativos pelo líquen Cladonia substellata Vainio). Objetivando comparar a atividade antimicrobiana de extratos brutos de Cladonia substellata, proveniente dos Estados de Minas Gerais e Pará, Brasil, utilizou-se o método de difusão em meio sólido. Extratos etéreo, clorofórmico e acetônico foram testados contra patógenos humanos e fitopatógenos na concentração de 1,0 mg/mL, 0,1 mg/mL e 0,01 mg/mL. Os extratos foram submetidos à cromatografia em camada delgada, e o princípio ativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…This can be explained by the composition of the organic extract of C. substellata originating from the Northeast of Brazil, with approximately 98% usnic acid in its composition (Huovinen & Ahti 1986, Ahti et al 1993, Yano-Melo et al 1999). This may be primarily responsible for the antimicrobial activity demonstrated in this study and others (Burkholder et al 1944, Carrazzoni 1975, Huovinen & Ahti 1986, Ahti et al 1993, Lauterwein et al 1995, Pereira et al 1997, Honda & Vilegas 1998, Yano-Melo et al 1999, Donlan 2001, Falcão et al 2004, Ribeiro et al 2006, Moura et al 2008. Ranković et al (2012) tested the antibacterial activity of usnic acid compared to streptomycin for Bacillus mycoides (ATCC 6462), B. subtilis (ATCC 6633), S. aureus (ATCC 25923), Escherichia coli (ATCC 25922), and Klebsiella pneumoniae (ATCC 13883).…”
Section: Determination Of Antibacterial Activity Of Organic Extract Osupporting
confidence: 59%
See 1 more Smart Citation
“…This can be explained by the composition of the organic extract of C. substellata originating from the Northeast of Brazil, with approximately 98% usnic acid in its composition (Huovinen & Ahti 1986, Ahti et al 1993, Yano-Melo et al 1999). This may be primarily responsible for the antimicrobial activity demonstrated in this study and others (Burkholder et al 1944, Carrazzoni 1975, Huovinen & Ahti 1986, Ahti et al 1993, Lauterwein et al 1995, Pereira et al 1997, Honda & Vilegas 1998, Yano-Melo et al 1999, Donlan 2001, Falcão et al 2004, Ribeiro et al 2006, Moura et al 2008. Ranković et al (2012) tested the antibacterial activity of usnic acid compared to streptomycin for Bacillus mycoides (ATCC 6462), B. subtilis (ATCC 6633), S. aureus (ATCC 25923), Escherichia coli (ATCC 25922), and Klebsiella pneumoniae (ATCC 13883).…”
Section: Determination Of Antibacterial Activity Of Organic Extract Osupporting
confidence: 59%
“…It also acts as an insecticide, moisturizer, antihistamine, and agent that offers protection from the harmful effects of lightning UV (Fournet et al 1997, Cochietto et al 2002, Ingólfsdóttir 2002, Falcão et al 2004, Ribeiro et al 2006, Honda et al 2010. In humans, a hepatotoxic effect was observed when it was used systemically (Moura et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The standard chloramphenicol presented activity in almost all bacterial strains tested, except Listeria monocytogenes and Escherichia coli, being the persistent results in the three techniques use Previous research had reported antibacterial activity in several lichen species against Gram-positive and Gram negative bacterias in a wide variety of concentrations, under some technique used. [24][25][26][27] Some authors indicate that the vast majority of lichens are more active against Gram-positive than Gram-negative bacteria. 5,23 The difference in sensitivity between bacterias can be attributed to the different composition of the cell walls that exists between these microorganisms (varying permeability), which in some cases blocks the entry of certain compounds into the cellular interior.…”
Section: In Vitro Assays: Spot-on-a-lawn Method Disc Diffusion and Wmentioning
confidence: 99%
“…Lichen extracts are mixtures of different compounds, and their antimicrobial activity is not only the result of the different activities of individual components but may be the result of their interactions, which can have different effects on the overall activity of extracts. Ribeiro et al (2006) also reported action of ether extract from C. substellata against human and plant pathogenic bacteria and supposed a synergic action between their components. Martins et al (2010) also showed a synergic action of organic extract of C. aggregata against S. aureus.…”
Section: In Vitro Antioxidant and Antimicrobial Properties Of Organicmentioning
confidence: 98%